Type I hair cells of striolar and central zones in vestibular organs are essential for head stability and postural control - Kazuya Ono; Hyun Jae Lee; Hui Ho Vanessa Chang; Brandie Morris Verdone; Talah Wafa; Youngrae Ji; Austin Huang; Tracy Fitzgerald; Kathleen E. Cullen; Doris K. Wu (Proceedings of the National Academy of Sciences, 2026)
The vestibular system of the inner ear provides head motion and orientation information required for maintaining balance and spatial orientation. Each of the five vestibular sensory organs contains type I and type II hair cells (HCs). Type I HCs are particularly notable for their evolutionary adaptability and unique calyceal synapses, in which the vestibular afferent nerve ending envelopes the HC body. In vitro studies indicate that calyceal synapses can transduce signals from HCs to afferents via nonquantal transmission, a mechanism proposed to be faster than conventional bouton synaptic transmission. In specialized regions of vestibular organs—striolae and central zones—many afferents form calyces that encase multiple type I HC bodies, suggesting that nonquantal transmission could be especially important in these regions. Consistently, striolar/central zone afferents are thought to preferentially mediate rapid and high-frequency stimulations. However, the direct consequences of selectively losing these HCs remain unknown. Here, we investigated the role of type I HCs within striolar/central zones by genetically ablating these cells. Reduction of type I HCs in these regions led to a loss of calyces and a compensatory increase in striolar type II HCs. These mutants exhibit reduced vestibular-evoked potentials, a response driven predominantly by striolar activity. In contrast, the vestibulo-ocular reflex, which is thought not to require striolar/central zone function, remained intact. Furthermore, loss of striolar/central zone-specific type I HCs causes head tremor in pups and abnormal head motion in adults, indicating that these HCs are essential for mediating head stability and postural control.